PEMANFAATAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN BERBICARA MENYAMPAIKAN LAPORAN SECARA NARATIF : Penelitian Eksperimen Kuasi terhadap Siswa Kelas XI SMK Tunas Bangsa Ciater Tahun Ajaran 2012/2013 - Wiguna , Anggi Setia (2013)
This paper is entitled "Ajén Palsapah dina Upacara Jaroh di Kampung Dukuh Désa Ciroyom Kabupatén Garut pikeun Bahan Pangajaran Maca Bahasan di SMA Kelas XI". The study is aimed to describe (1) origin of the occurrence Jaroh ritual tradition in Dukuh village; (2) the implementation procedure of Jaroh ritual in Dukuh village; (3) the philosophy values which are carried by Jaroh ritual; (4) the elements of culture which are carried by Jaroh ritual; and (5) the implicature of Jaroh ritual towards reading learning materials in senior high school. The study uses descriptive qualitative methodology with literature review technique, interview, observation, and documentation. The instruments which are used in collecting data are recorder, camera, and interview guidance. Jaroh ritual tradition is one of culture tradition which exists in Dukuh, Ciroyom village, Garut regency. The reason of Jaroh ritual still exists is an implementation of gratitude to Syekh Abdul Jalil who had spread and preached Islam religion in Dukuh village. The ritual was held in Syekh Abdul Jalil cemetery in every Saturday. The ritual was started when the citizen gathered around in Bale Ageung, and continued by mandi cebor, afterwards the people began to enter cemetery area. Inside cemetery area, the caretaker of cemetery led to take a pray and solawat with all the people. And then the people did the Jaroh ritual by gathering in front of Syekh Abdul Jalil's cemetery while took a pray. Jaroh ritual was ended by eating together in caretaker's house. The study found that there are philosophy values which are carried by Jaroh ritual, including 1) system of religion, 2) system of social organization, 3) system of knowledge, 4) art, 5) system of livelihood, and 6) system of technology. Philosophy values of Jaroh ritual in Dukuh village are part of Sundanese culture, and it can be used as learning material in Sundanese language and literature, especially reading learning material for 11th grade. Judul penelitian ini adalah "Pemanfaatan Media Audio Visual pada Pembelajaran Berbicara Menyampaikan Laporan Secara Naratif (Penelitian Eksperimen Kuasi terhadap Siswa Kelas XI SMK Tunas Bangsa Ciater tahun ajaran 2012/2013). Penelitian ini beranjak dari pokok permasalahan: (a) bagaimana kemampuan berbicara dalam menyampaikan laporan secara naratif siswa sebelum mengikuti pembelajaran dengan menggunakan media audio visual?; (b) bagaimana kemampuan berbicara dalam menyampaikan laporan secara naratif siswa sesudah mengikuti pembelajaran dengan menggunakan media audio visual?; (c) apakah media audio visual efektif digunakan dalam pembelajaran berbicara menyampaikan laporan secara naratif? Tujuan dilaksanakannya penelitian ini, 1) mendeskripsikan kemampuan berbicara menyampaikan laporan secara naratif siswa sebelum mengikuti pembelajaran dengan menggunakan media audio visual; 2) mendeskripsikan kemampuan berbicara menyampaikan laporan secara naratif siswa sesudah mengikuti pembelajaran dengan menggunakan media audio visual; dan 3) mendeskripsikan perbedaan yang signifikan antara hasil pembelajaran berbicara menyampaikan laporan secara naratif sebelum dan setelah menggunakan media audio visual. Penelitian ini dilakukan dengan menggunakan metode eksperimen kuasi, dengan desain the one group pre-test-post-test design, yaitu satu kelompok mendapat perlakuan, pengukuran dilakukan sebelum dan sesudah perlakuan diberikan, dan pengaruh perlakuan diukur dari perbedaan antara pengukuran awal dan akhir pengukuran. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMK Tunas Bangsa Ciater. Sampel dalam penelitian ini adalah XI Tata boga 1 SMK Tunas Bangsa Ciater yang berjumlah 20 orang. Instrumen yang penulis gunakan dalam mengumpulkan data adalah instrumen tes dan instrumen perlakuan dengan menganalisis data menggunakan uji statistika yang diperoleh dari data prates dan pascates. Dari perhitungan yang telah dilakukan diperoleh thitung (10,76) > ttabel (2,093), sehingga dapat disimpulkan bahwa Ho ditolak (H1 diterima). Artinya, media pembelajaran terbukti efektif digunakan dalam pembelajaran berbicara menyampaikan laporan secara naratif. Dibuktikan oleh perbedaan hasil rata-rata prates dan pascates yaitu dengan perolehan nilai rata-rata prates sebesar 52,9 dan perolehan pascates sebesar 69,15. The title of this research is "Exploiting Audio Visual Media in Learning Speaking a Report On Narrative ( Quasi Experimental Research on Class XI students of SMK Tunas Bangsa Ciater academic year 2012/2013 ) . Research was moved from the main issues : ( a) how the ability to speak in delivering narrative reports of students before following study using audio-visual media ? , (b ) how the ability to speak in conveying narrative report after participating student learning by using audio- visual media ? ; ( c ) whether the audio- visual media are used in learning to speak effectively deliver a report in the narrative ? Purpose of the implementation of this study , 1 ) describes the ability of speaking convey narrative reports of students before following study using audio- visual media ; 2 ) submit a report describing the ability to speak after following narrative student learning by using audio- visual media , and 3 ) describe the significant differences between learning outcomes narrative speaks submit reports before and after the use of audio- visual media . This research was conducted using quasi-experimental methods , the design of the one group pre - test - post-test design , in one group received treatment , measurements were performed before and after treatment was given , and the effect of treatment was measured from the difference between initial and final measurement measurement . The population in this study were all students of class XI SMK Tunas Bangsa Ciater . The sample in this study is the first XI SMK Tunas Bangsa Tataboga Ciater totaling 20 people's . The instruments I use in collecting the data is a test instrument and treatment instrument by analyzing the data using a statistical test that the data obtained from the pre-test and post-test . Of the calculations have been done obtained t ( 10.76 ) > t table ( 2.093 ) , so it can be concluded that Ho is rejected ( H1 accepted ) . That is, prove effective use of instructional media in teaching speaking convey narrative report's . Evidenced by the difference in the average yield of the pre-test and post-test with average grades of 52.9 and a pre-test post-test gains of 69.15 .